Guided acousticwave brillouin scattering in a nanostructure core fiber - Beugnot, Jean Charles; Delqué, Michaël; Stiller, Birgit; Lee, Min Won; Maillotte, Hervé; Laude, Vincent; Mélin, Gilles; Sylvestre, Thibaut (Optics InfoBase Conference Papers, 2010)
We study guided acoustic wave Brillouin scattering in a nanostructure core fiber. Such design is shown, experimentally and numerically, to allow for the trapping of several acoustical modes overlapping efficiently with the optical one. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29